Fluid management in acute lung injury and ards - Roch, Antoine (Springer, 2011)
ARDS is particularly characterized by pulmonary edema caused by an increase in pulmonary capillary permeability. It is considered that limiting pulmonary edema or accelerating its resorption through the modulation of fluid intake or oncotic pressure could be beneficial. This review discusses the principal clinical studies that have made it possible to progress in the optimization of the fluid state during ARDS. Notably, a randomized, multicenter study has suggested that fluid management with the goal to obtain zero fluid balance in ARDS patients without shock or renal failure significantly increases the number of days without mechanical ventilation. On the other hand, it is accepted that patients with hemodynamic failure must undergo early and adapted vascular filling. Liberal and conservative filling strategies are therefore complementary and should ideally follow each other in time in the same patient whose hemodynamic state progressively stabilizes. At present, although albumin treatment has been suggested to improve oxygenation transiently in ARDS patients, no sufficient evidence justifies its use to mitigate pulmonary edema and reduce respiratory morbidity. Finally, the resorption of alveolar edema occurs through an active mechanism, which can be pharmacologically upregluated. In this sense, the use of beta-2 agonists may be beneficial but further studies are needed to confirm preliminary promising results.